The association of Ideas and the concept of the Picturesque in the British Aesthetics of the Enlightment - Murcia Serrano, Inmaculada (Pensamiento. Revista de Investigación e Información Filosófica, 2021)
With the pretext of reviewing the meaning and theoretical implications of the coinage, in the eighteenth century, of the concept of the picturesque, I attempt to settle with a new perspective the thesis that the British aesthetic of the Enlightenment undergoes a remarkable turn towards subjectivity as a place of experimentation and artistic creation. To do this, I study, first of all, the empiricist epistemological mechanism that covers, to a large extent, the invention and development of the picturesque, that of the association of ideas, without which it is impossible to understand — and this is the second issue — the complexity of the term «picturesque» and its relevance for the modern turn of aesthetics toward subjectivity.
Keywords: association of ideas; british empiricism; the picturesque; aesthetics